1975
DOI: 10.1038/bjc.1975.96
|View full text |Cite
|
Sign up to set email alerts
|

T and B cell populations in blood and lymph node in lymphoproliferative disease

Abstract: Summary.-Lymph node and peripheral blood lymphocytes were studied simultaneously for surface markers of T and B cells in 22 patients with lymphoproliferative diseases and 8 patients with non-neoplastic lymphadenopathy. This resulted in the classification of the malignancy from involved lymph nodes into 4 groups. Six patients had B cell lymphomata with normal or strong immunofluorescent staining for surface membrane immunoglobulin; 8 patients had B cell chronic lymphocytic leukaemia with pale staining for surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1976
1976
1982
1982

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…The present investigations confirm the opinion that most lymphoproliferative diseases of the non-Hodgkin type represent a variety of disorders in the differentia tion of the B cell series [6,17,18], whereas lymphoma classified as T cell in origin are very rare.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present investigations confirm the opinion that most lymphoproliferative diseases of the non-Hodgkin type represent a variety of disorders in the differentia tion of the B cell series [6,17,18], whereas lymphoma classified as T cell in origin are very rare.…”
Section: Discussionsupporting
confidence: 88%
“…The results obtained from the blood lymphocytes of healthy donors are within the normal range found by others [6,20]. In our study, surface marker charac teristics of lymphocytes from normal lymph nodes and normal blood were very similar and indicate a distint T cell predominance [10].…”
Section: Discussionsupporting
confidence: 86%
“…The Fc-receptor-bearing lym phocyte population on the other hand was less than that found in peripheral blood (23 ± 4°/o) but the C3-receptor-bearing popu lation was on average higher than that found in peripheral blood (33 ± 6%) and in all but one case was always higher than the corresponding value for the Fc population. Mavligit et al [1975] reported their find ings in normal mesenteric nodes from a pa- Cooper et al [1975] in their study of T and B cell populations in blood and lymph node in lymphoproliférative disease report ed a T cell count of 26 and 63% in two nor mal nodes removed during elective surgery. The corresponding Fc-receptor value was 3 and 21%.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports dealing with thymus, tonsil [Brown and Greaves, 1974a, b], bone marrow [Borella and Sen, 1974] and spleen [Habeshaw and Stuart, 1974;Kaur et al, 1974] have re cently appeared in the literature, and also a few studies dealing with surface markers on malignant lymphocytes in lymph nodes and spleens of patients with lymphoproliférative diseases [Peter et al, 1974;Cooper et al, 1975]. Reports of lymphocyte subpopula tions in normal lymph nodes [Papamichael et al, 1971;Verma et al, 1971] or in re gional nodes draining solid tumours [7iafc-raklides et al, 1974;Richters and Kasper sky, 1975] have, however, been rather in frequent.…”
Section: Introductionmentioning
confidence: 99%
“…The second is to assess the maturity of the B cell by a number of cell surface markers, and the third is to relate the surface markers to the histology of the tumour. Previous attempts to identify the cells present in human lymphomas by surface marker techniques (Brouet, Labaume and Seligmann, 1975;Cooper et al, 1975;Dorfman, 1975;Gajl-Peezalska, Bloomfield and Sosin, 1975;Habeshaw and Stuart, 1975;Jaffe et al, 1975;Huang et al, 1974;Peter, Mackenzie and Glassy, 1974;Stuart and Habeshaw, 1976;Smith et al, 1973) have all shown that most non-Hodgkin lymphomas consist predominantly of B cells, with a minority of T cells. A few are derived from T cells, and those arising from macrophages are distinctly uncommon.…”
mentioning
confidence: 99%